Altered Natural Killer Cell Function in HIV-Exposed Uninfected Infants - Smith, Christiana; Jalbert, Emilie; de Almeida, Volia; Canniff, Jennifer; Lenz, Laurel L.; Mussi-Pinhata, Marisa M.; Cohen, Rachel A.; Yu, Qilu; Amaral, Fabiana R.; Pinto, Jorge; Alarcon, Jorge O.; Siberry, George; et al. (Frontiers in Immunology, 2017)
Objectives: HIV-exposed uninfected (HEU) infants have higher rates of severe and fatal infections compared with HIV-unexposed (HUU) infants, likely due to immune perturbations. We hypothesized that alterations in natural killer (NK) cell activity might occur in HEU infants and predispose them to severe infections. Design: Case-control study using cryopreserved peripheral blood mononuclear cells (PBMCs) at birth and 6 months from HEU infants enrolled from 2002-2009 and HUU infants enrolled from 2011-2013. Methods: NK cell phenotype and function were assessed by flow cytometry after 20 hour incubation with and without K562 cells. Results: The proportion of NK cells among PBMCs was lower at birth in 12 HEU vs. 22 HUU (1.68% vs. 10.30%, p<0.0001) and at 6 months in 52 HEU vs. 72 HUU (3.09% vs. 4.65%, p=0.0005). At birth, HEU NK cells demonstrated increased killing of K562 target cells (p<0.0001) and increased expression of CD107a (21.65% vs. 12.70%, p=0.047); but these differences resolved by 6 months. Stimulated HEU NK cells produced less IFNγ at birth (0.77% vs. 2.64%, p=0.008) and at 6 months (4.12% vs. 8.39%, p=0.001), and showed reduced perforin staining at 6 months (66.95% vs. 77.30%, p=0.0008). Analysis of cell culture supernatants indicated that lower NK cell activity in HEU was associated with reduced IL-12, IL-15, and IL-18. Addition of recombinant human IL-12 to stimulated HEU PBMCs restored IFNγ production to that seen in stimulated HUU cultures. Conclusions: NK cell proportion, phenotype, and function are altered in HEU infants. NK cell cytotoxicity and degranulation are increased in HEU at birth, but HEU NK cells have reduced IFNγ and perforin production, suggesting an adequate initial response, but decreased functional reserve. NK cell function improved with addition of exogenous IL-12, implicating impaired production of IL-12 by accessory cells. Alterations in NK cell and accessory cell function may contribute to the increased susceptibility to infection in HEU infants.